Tinjauan Yuridis Perlindungan Konsumen atas Keterlambatan Pengiriman Barang oleh Jasa Ekspedisi - Dzulhaq, Akhmad Faris; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The growth of e-commerce in Indonesia has increased shipping volumes alongside consumer complaints regarding delivery delays. This legal-doctrinal study aims to analyze the legal relationship between consumers and shipping services, legal protection, and the construction of corporate liability for delivery delays. Utilizing statutory and conceptual approaches, the analysis relies on the Civil Code, Commercial Code, Consumer Protection Act, and Postal Act. The results indicate that the legal relationship stems from a consensual contract of carriage via standard clauses, weakening consumer bargaining power. Delivery delays without force majeure constitute a breach of contract, triggering compensation rights under Article 19 of the Consumer Protection Act. The carrier’s liability follows the fault-based principle (fault liability) with specific limitations that must not negate fundamental consumer rights. Dispute resolution is accessible through non-litigation or litigation channels. This study recommends strengthening supervision over standard shipping clauses and harmonizing regulations for damages caused by delivery delays.